Rancang Bangun Game Kartu Spirit Berbasis Android dengan Fitur Online Multiplayer - Jodi Pratama, Agung; Kompiang Oka Sudana, A.A.; Piarsa, I Nyoman (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.1 April 2015, 2015)
The development of game as entertainment is growing rapidly. Digital game that used to be played only in console, now can be played in computer and even a mobile device especially Android. Spirit Card Game is one of the most famous card game in Bali. This game is played with maximum of 8 players and one of them was assigned as dealer. Winner is declared when player’s card value is bigger than dealer’s card value. Android device is used as the media to play the game with online multiplayer feature based on client-server architecture. Android devices which connected to Internet can login with Facebook account or as a guest then create a room or join a room in order to play. The game started with the dealer deals first card to every player in room, then deals second card to player while every player places their bet, and the last is the dealer deals third card to players that call an optional card. Bet is paid in the final turn of the round.The performance of application is assessed by questionnaire survey in four aspect. User Interface Aspect is assessed with good performance by 36% of votes, Software Engineering by 55%, Entertainment by 49%, and Content by 50%.
Keywords: Game; Android; Multiplayer; Kartu; Client-server